Finding and tracing human MSC in 3D microenvironments with the photoconvertible proteinDendra2 - Caires, HR (2015)
Mesenchymal Stem/Stromal Cells (MSC) are a promising cell type for cell-based therapies - from tissue regeneration to treatment of autoimmune diseases - due to their capacity to migrate to damaged tissues, to differentiate in different lineages and to their immunomodulatory and paracrine properties. Here, a simple and reliable imaging technique was developed to study MSC dynamical behavior in natural and bioengineered 3D matrices. Human MSC were transfected to express a fluorescent photoswitchable protein, Dendra2, which was used to highlight and follow the same group of cells for more than seven days, even if removed from the microscope to the incubator. This strategy provided reliable tracking in 3D microenvironments with different properties, including the hydrogels Matrigel and alginate as well as chitosan porous scaffolds. Comparison of cells mobility within matrices with tuned physicochemical properties revealed that MSC embedded in Matrigel migrated 64% more with 5.2 mg protein/mL than with 9.6 mg/mL and that MSC embedded in RGD-alginate migrated 51% faster with 1% polymer concentration than in 2% RGD-alginate. This platform thus provides a straightforward approach to characterize MSC dynamics in 3D and has applications in the field of stem cell biology and for the development of biomaterials for tissue regeneration.